Comparison of Adhesion of Soft-Liner between Conventional PMMA and 3D Printed Resin Denture Bases - Dawood Jadaan; Juzailah Roffie; Husniyati Roslan; Nahas P (Dentistry 3000)
Aims: The purpose of this study was to evaluate the tensile strength of the soft-liner (Molloplast-B®) between the denture foundation made of 3D printed resin and traditional acrylic (PMMA).